HYDROCHEMISTRY OF THE WATERS CIRCULATING IN THE CRATER, EASTERN AND SOUTHERN SLOPES OF ARAGATS VOLCANO (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
This study examines the hydrochemistry of mineral and freshwaters circulating in the crater of the Aragats volcano and on its Еastern and Сouthern slopes, as well as to clarifying several related issues. On the Еastern slopes, in connection with the composition of the mineral waters, a natural acid drainage phenomenon has been observed, which propagates downstream along the main tributary and gradually diminishes within the territory of the Tsaghkashen Village. In this area, noticeable differences are also observed in the compositions of waters discharging from outlets located in proximity to one another, which may be explained by the substantial difference in the depths of formation of the mineral and freshwater bodies, as well as by the isolation of their respective pathways to the Earth's surface. The most widespread and dominant water types were distinguished for the investigated sites, and their chemical formulas were determined according to Kurlov's classification.
Keywords: hydrochemistry; Aragats volcano; mineral water; oxygen barrier; water composition; mineralization; natural acid drainage